2011
DOI: 10.1177/0021998311410494
|View full text |Cite
|
Sign up to set email alerts
|

Melting and nonisothermal crystallization behavior of polypropylene/hemp fiber composites

Abstract: Melting and nonisothermal crystallization behaviors of polypropylene (PP) and PP/hemp fibers (HFs) composites was investigated by differential scanning calorimetry (DSC) technique. The results show that the incorporation of HFs increases both the melting temperature (T m ) and crystallization temperature (T c ) of PP. Moreover, in comparison with PP/HF(70/30) composite, the addition of maleic anhydride-grafted PP (PP-MAH) results in a slight decrease in T m but a significant increase in T c of PP. The higher T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Studies have demonstrated that the influence of the reinforcing fibers on crystallization is not only fiber-specific but also strongly dependent upon surface conditions (Ning et al 2012). Nevertheless, it has been generally accepted that in reinforced thermoplastics, natural fibers can act as heterogenous nucleating agents (Arbelaiz et al 2006;Pengfei et al 2011). The capacity of natural fibers to act as nucleating agents might explain the slight increase in crystallinity detected when comparing composites with increasing fiber content.…”
Section: Peer-reviewed Articlementioning
confidence: 99%
“…Studies have demonstrated that the influence of the reinforcing fibers on crystallization is not only fiber-specific but also strongly dependent upon surface conditions (Ning et al 2012). Nevertheless, it has been generally accepted that in reinforced thermoplastics, natural fibers can act as heterogenous nucleating agents (Arbelaiz et al 2006;Pengfei et al 2011). The capacity of natural fibers to act as nucleating agents might explain the slight increase in crystallinity detected when comparing composites with increasing fiber content.…”
Section: Peer-reviewed Articlementioning
confidence: 99%
“…It is observed that rate constant k for the PP phase in unmodified MWCNTs based composite (P23Tx composite) is higher than that of P23T5L5Mx composite (see Supporting Information Table 2). It is also to be noted that though the Li‐AHA concentration is increased, however the addition of PP‐ g ‐MA in the same extent in all the modified composition has increased the melt‐viscosity of the composite (due to the melt‐interfacial interaction) that delayed the crystallization process to some extent . Moreover, Prashantha et al observed that PP‐ g ‐MA may also form a coating on the surface of nanotubes that may also decrease the nucleation rate of the MWCNTs for the PP.…”
Section: Resultsmentioning
confidence: 99%
“…During the crystallization of MB, F(t) decreased from 5.42 to 3.37 when the PP is added to MB, indicating that PP act as nucleating agent [35,43,44]. By other hand, when the fibre is added to MB, F(t) increased showing a retarding effect [35,45]. The same applies when the fibre is added to MB/ PP system.…”
Section: Modelling Of Non-isothermal Crystallization Processmentioning
confidence: 90%